The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0253968
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of vacuum-formed retainers and Hawley retainers on periodontal health: A systematic review and meta-analysis

Abstract: Background Recently, increasing attention has been paid to the periodontal health of orthodontic patients in the maintenance stage in clinical practice. The focus of this meta-analysis was to compare the effects of vacuum-formed retainers (VFR) and Hawley retainers (HR) on periodontal health, in order to provide a reference for clinical selection. Methods From the establishment of the database until November 2020, a large number of databases were searched to find relevant randomized control trials, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Fixed retainers have been associated with a greater accumulation of dental plaque and calculus, and with minimally worse, albeit clinically unimportant, gingivitis in comparison with VFRs [97]. Moreover, patients using Hawley appliances may end up in an even better periodontal condition compared with those using VFRs [98]. Eroglu et al (2019) [99] found fixed and removable orthodontic retainers not statistically significantly different regarding the plaque index, the gingival index, bleeding on probing, and probing depth values.…”
Section: Discussionmentioning
confidence: 95%
“…Fixed retainers have been associated with a greater accumulation of dental plaque and calculus, and with minimally worse, albeit clinically unimportant, gingivitis in comparison with VFRs [97]. Moreover, patients using Hawley appliances may end up in an even better periodontal condition compared with those using VFRs [98]. Eroglu et al (2019) [99] found fixed and removable orthodontic retainers not statistically significantly different regarding the plaque index, the gingival index, bleeding on probing, and probing depth values.…”
Section: Discussionmentioning
confidence: 95%
“…Comparing the removable appliances, HRs provide better settling of the occlusion compared with VFRs, and they also seem to be more durable in terms of breakage [ 7 , 48 , 56 , 57 ]. Bowen Li et al concluded in their systematic review that patients using HRs showed healthier periodontal condition than those using VFRs [ 58 ]. In contrast to this, VFRs are more aesthetic, do not interfere with speech and are therefore more acceptable to the patient [ 55 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of post-treatment stability, patient satisfaction, and survival time, there seems to be no evidence to support the use of thermoplastic retainers over Hawley retainers [19] . Furthermore, patients wearing thermoplastic retainers are shown to be more prone to gingival inflammation [20] . The increasing use of plastic materials in orthodontics may be alarming and adds to the growing concern about plastic pollution worldwide [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, systematic reviews show insufficient evidence to support the use of thermoplastic retainers over Hawley retainers in terms of effectiveness, survival time, and patient satisfaction [17][18][19] . In addition, the most recent meta-analysis concludes that in the short term, thermoplastic retainers have more adverse effects on periodontal health than Hawley retainers [20] .…”
Section: Introductionmentioning
confidence: 99%